Internalization of Discipline Values through the Tahfidzul Qur'an Program at SD Ummu Aiman Lawang - Aziz, Wafikul; Safi’i, Imam; Sari Dewi, Mutiara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research aims to describe the internalization of discipline character values through the Tahfidzul Qur'an program at SD Ummu Aiman Lawang in 2025. This study uses a qualitative approach with a case study method focused on three main aspects: planning, implementation, and program evaluation. Data were obtained through observation, in-depth interviews, and documentation involving the school principal, tahfidz teachers, and students. The research results show that the internalization of discipline values is carried out systematically through school policies, habituation of religious activities, and teacher role modeling in building a culture of discipline. Discipline values are reflected in time management, responsibility for memorization, and consistency of student attendance in tahfidz activities every morning. Evaluation is conducted formatively and summatively with an emphasis on character formation, not just on memorization achievement. The findings of this research confirm that the tahfidz program has a significant contribution to the formation of discipline character in elementary school students based on Islamic values and provides implications for the development of character education in Islamic educational institutions.